2017
DOI: 10.1164/rccm.201602-0272oc
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Maternal Stress and Depression, Type 2 Responses, and Recurrent Wheezing at Age 3 Years in Low-Income Urban Families

Abstract: Rationale: Maternal depression and prenatal and early life stress may influence childhood wheezing illnesses, potentially through effects on immune development.Objectives: To test the hypothesis that maternal stress and/or depression during pregnancy and early life are associated with recurrent wheezing and aeroallergen sensitivity and altered cytokine responses (enhanced type 2 or reduced virus-induced cytokine responses) from stimulated peripheral blood mononuclear cells at age 3 years.Methods: URECA (Urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 37 publications
(44 reference statements)
5
43
1
Order By: Relevance
“…Reyes et al found that antenatal psychological distress predicted recurrent wheeze in early stages of life, in both independent and adjusted models. In addition, Ramratnam et al, and Mathilda Chiu et al, found that antenatal depression was significantly associated with recurrence of child wheeze. As these studies were conducted in HIC, urban, low‐income, and genetically predisposed children, they attributed the associations to biological mechanisms, such as the release of stress hormones, which affect foetal development in utero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reyes et al found that antenatal psychological distress predicted recurrent wheeze in early stages of life, in both independent and adjusted models. In addition, Ramratnam et al, and Mathilda Chiu et al, found that antenatal depression was significantly associated with recurrence of child wheeze. As these studies were conducted in HIC, urban, low‐income, and genetically predisposed children, they attributed the associations to biological mechanisms, such as the release of stress hormones, which affect foetal development in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal or postnatal maternal psychosocial risk factors have been reported to be associated with development of child wheeze, but there is sparse data from low and middle‐income countries (LMIC). Most research has been conducted in HIC, and predominantly in high‐risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…Putative mechanisms linking stress in pregnancy and childhood wheezing and asthma—independent of an effect on infections—include a dysregulation of maternal and child hypothalamic‐pituitary‐adrenal axes and an immune dysregulation in offspring . However, this mechanism more easily explains an enhanced susceptibility to childhood atopic disorders, including asthma, rather than wheezing in infancy …”
Section: Discussionmentioning
confidence: 99%
“…3 A number of factors affect early-life immune responses, including season of birth, 57 sex, 8 maternal stress, 9 and allergen and microbial exposures (farms, dog, cockroach, and endotoxin) during pregnancy and early life. 7,10 Reduced IFN-γ responses in cord blood and early infancy have been linked to the risk of LRTIs and recurrent wheezing in multiple cohorts.…”
Section: Perinatal Risk Factorsmentioning
confidence: 99%